Improved flotation of molybdenite from talc using a selective reagent scheme. (January 2022) - Zhang, Wanjia; Tao, Liming; Xun, Luobing; Qi, Zhongxu; Pooley, Stephen; Sun, Wei; Cao, Jian; Gao, Zhiyong
Graphical abstract: Highlights: Pullulan (PU) has a strong adsorption on both talc and molybdenite. Butyl xanthate (BX) desorbs pre-adsorbed PU on molybdenite, but not on talc. A reagent scheme (PU + BX) for separating molybdenite from talc was proposed. Abstract: Talc is one of the most problematic gangue minerals for molybdenite flotation owing to its strong natural hydrophobicity. In this work, pullulan polysaccharide (PU) was evaluated as a potential depressant in the flotation separation of molybdenite from talc. Bench flotation tests of single mineral samples and multi-mineral samples were carried out to evaluate the performance of PU in flotation. And the results show that under the preferable reagent scheme of 40 mg/L PU, 160 mg/L butyl xanthate (BX) and 25 μL/L MIBC, molybdenite can be effectively separated from talc over a wide pH range (from 2.0 to 8.0). Furthermore, FTIR and XPS analyses demonstrate that BX can desorb the pre-adsorbed PU on the surface of the molybdenite by competitive adsorption, but has only a slight effect on the PU adsorbed on surface of the talc. The results also confirm that PU has a strong and stable adsorption on the surfaces of talc and molybdenite, whereas BX adsorbs more strongly on the surface of molybdenite. Hence, the reagent scheme of PU + BX, with biodegradability, low toxicity, low cost and synergistic selectivity, has great potential for industrial application in the flotation separation of molybdenite from talc.